Chhaanch Nogori mold town: revival of metal craft in Dhamrai, Bangladesh - Bonotulshi, Doito (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.